Mesenchymal Stromal Cells and Their Extracellular Vesicles Enhance the Anti-Inflammatory Phenotype of Regulatory Macrophages by Downregulating the Production of Interleukin (IL)-23 and IL-22 - Hyvärinen, Kati; Holopainen, Minna; Skirdenko, Vita; Ruhanen, Hanna; Lehenkari, Petri; Korhonen, Matti; Käkelä, Reijo; Laitinen, Saara; Kerkelä, Erja (Frontiers in Immunology, 2018)
Resolution-phase macrophage population orchestrates active dampening of the inflammation by secreting anti-inflammatory and proresolving products including interleukin (IL)-10 and lipid mediators. We investigated the effects of both human bone marrow-derived mesenchymal stromal cells (MSCs) and MSC-derived extracellular vesicles (MSC-EVs) on mature human regulatory macrophages (Mregs). The cytokines and lipid mediators were determined from cell culture media of Mregs cultivated with MSCs and MSC-EVs. Additionally, the alterations in the expression of cell surface markers and the phagocytic ability of Mregs were investigated. Our novel findings indicate that both MSC co-culture and MSC-EVs down-regulated the production of IL-23 and IL-22 enhancing the anti-inflammatory phenotype of Mregs and amplifying proresolving properties. The levels of prostaglandin E2 (PGE2) were substantially upregulated in MSC co-culture media, which may endorse proresolving lipid mediator class switching. Additionally, our results manifest, for the first time, that MSC-EVs mediate the Mreg phenotype change via PGE2. These data suggest that both human MSC and MSC-EVs may potentiate tolerance-promoting proresolving phenotype of human Mregs.